(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Essay is a popular genre of English literature, influencing other literatures all over the world. The essay is any short composition in prose that discusses a matter, expresses a point of view, persuades us to accept a thesis or simply entertains us. The essay is smaller than a dissertation or treatise, and it is not comprehensive, and unlike the other, it entertains the general readers. It is informal, making use of such literary devices as anecdote, illustration and humor. The formal essay (also called article) is impersonal and orderly as we notice in magazines and journals. The personal essay speaks of the author’s autobiographical narration, sometimes whimsical.